Conversations on a Bench - Owen Sheers (www.bbc.co.uk/programmes/b07z3hpt, 2016)
a specially commissioned work by poet Owen Sheers draws on the voices and stories of those who sit and contemplate the inscription, "Born to be Wild - Dinks Nash -Loved Forever."